Facets of Subjective Health From Early Adulthood to Old Age. (February 2017) - Franz, Carol E.; Finkel, Deborah; Panizzon, Matthew S.; Spoon, Kelly; Christensen, Kaare; Gatz, Margaret; Kremen, William S.; Krueger, Robert; Neiderhiser, Jenae; Reynolds, Chandra; Pedersen, Nancy L.; ,
Objective: Subjective health is a complex indicator predicting longevity independent of objective health. Few studies examine genetic and environmental mechanisms underlying different facets of subjective health across the life course.Method: Three subjective health measures were examined in 12, 900 twins ( M age = 63.38, range = 25-102) from nine studies in the Interplay of Genes and Environment across Multiple Studies Consortium: self-rated health (SRH), health compared with others (COMP), and health interfering with activities (ACT).Results: Analyses indicated age and sex differences in mean scores depending on the measure. SRH and ACT showed significant linear and non-linear moderation by age for individual differences in both genetic and environmental variance. Significant sex differences in components of variance were found for SRH and ACT, but not COMP.Discussion: Subjective health appears to be dependent on frame of reference and reflect different aspects of health. Results suggest different genetic and environmental mechanisms underlie each facet.